Influence of shear displacement on heat transport in 3D rough-walled rock fractures - Jin, Yunzhe; Zou, Liangchao; Yao, Chi; Zhou, Chuangbing; Cvetkovic, Vladimir (Energy (Oxford), 2024)
Understanding the influence of shear displacement on heat transport in rock fractures is important for evaluating and optimizing heat extraction in enhanced geothermal systems. This study presents quantitative characterization of the heat transfer evolution in single fractures subject to shear displacement, aiming to demonstrate the impact of shear displacement on heat transport in natural rock fractures. The direct shear of rock fractures is directly simulated using the finite element method and the Mohr-Coulomb yield criterion. The shear simulation method is validated against laboratory shear test data from the literature. Shear simulations under different mechanical conditions, including different normal stresses and shear displacements, are conducted. The sheared fractures are then used to simulate fluid flow and heat transfer processes by directly solving the Navier-Stokes equations and the heat transport equation. The results show that shear displacements can cause significant changes in fracture aperture and subsequently enhance the heterogeneity of flow fields and temperature fields in the fracture. The heat transfer coefficient increases with the increasing of normal stress and Peclet number, while it decreases with the increase of shear displacement. The plastic deformation of fracture surfaces can significantly affect the heat transfer rate. The findings can help understand the heat transfer characteristics in natural rock fractures. •The higher normal stress and lower shear displacement lead to higher heat transfer coefficient.•The heat transfer coefficient of rock fractures increases with the increasing Péclet number.•Neglecting plastic deformation in shear will underestimate the heat transfer coefficient.